Pharmacies agent system using rule-based / Faraizura Razali - Razali, Faraizura (2004)
Pharmacists Agent System (PharmAS) is a web-based system which it will help to solve this problem using intelligent agent approach as an agent to all pharmacies in Shah Alam. This system will give suggestions to the users according to the criteria that they request such as name of the medicine, location of the pharmacies, type and usage by using rule-based method. Besides that, the users can also get detail information about each medicine. It is also useful to all pharmacies' customers and other people for those who want to know the about the medicine in the market. Besides that, it will be useful in emergency situation especially at night. Meanwhile, this system can be access through the Internet. The main objective of PharmAS is to design a user profile to stone user's medicinal requirement and to develop an agent that searches information on medicines from pharmacies based on user request from pharmacies in the area of Shah Alam only. Rule-based approach had been used to this develop this project. As a conclusion, it is found that the result and finding made are mostly gained from the construction phase.